EFFECT OF MAGNESIUM TREATMENT PROCESS ON THE PRODUCING COMPACTED GRAPHITECAST IRON WITH DIFFERENT CASTING THICKNESS - Ramadhani, Tama; Purwadi, Wiwik; Polonia, Betti Ses Eka; Yusuf, Yusuf (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
Strength, toughness, machinability and damping capacity are properties of compacted graphite iron thatdistinguish the properties between flake graphite cast iron and spheroidal cast iron. The formation of compactedgraphite can be set to achieve the required specification. The formation of compacted graphite is started fromspheroidal to compacted cast iron. The residual magnesium after magnesium treatment and the solidification ratehave a significant role in the formation of compacted graphite. The high content of residual magnesium canobstruct the graphite plane to grow during the transformation from spheroidal to compacted shape. In addition,the cooling rate of the casting can be controlled by varying the casting thickness. The compacted graphite in thecast iron are characterized according to shape, size ai`nd distribution. The optimum compacted graphite in thecast iron that can be produced has 30 mm of casting thickness with 0.017 % of residual magnesium.